Acute kidney injury induced by COVID-19: a literature review (Research, Society and Development, 2023)
Introduction: The COVID-19 infection has presented significant complications to individuals affected by the disease, among them, acute kidney injury has been showing an increasing incidence. Objective: to know the prevalence of kidney injuries associated with COVID-19, as well as its main clinical and laboratory manifestations. Method: A narrative literature review was performed using the Scientific Electronic Library Online (SciELO) and PubMed databases. For the search, the descriptors were used: “Sars-CoV-2”, “COVID-19” and “Acute Kidney Injury”. Complete articles were selected, published in the languages: English, Spanish and Portuguese, during the year 2020 to 2023. 482 scientific productions were pre-selected, of which 59 corresponded to the inclusion criteria: complete articles; in English, Portuguese and Spanish and related to the objective used in this study. Results and Discussion: Reports of previous outbreaks of severe acute respiratory syndrome described the prevalence of acute kidney injury, ranging from 5% to 15% of all cases, requiring the use of renal replacement therapy for 5% to 58% of critically ill patients. The impact of acute kidney injury on the outcomes of patients with SARS (SARS)-CoV-2 remains unclear but is of particular interest for introducing early therapy in acute patients as well as contributing to a better definition of prognosis. The extent (?) to which the development of acute kidney injury is associated with severe COVID-19 is unclear, given its association with relative immune dysregulation and exaggerated inflammatory responses. However, it is concluded that patients with the development of acute kidney injury have a worse prognosis and a higher mortality rate.